Implementasi Nisbah Bagi Hasil Produk Tabungan Haji Melalui Akad Mudharabah Pada Bank Syariah Indonesia KCP Stabat - Indah, Indah Aulia Putri (Jurnal Ekonomi dan Keuangan Syariah, 2022)
This research aims to find out the application and explain the mudharabah contract at Bank Syariah Indonesia KCP Stabat and find out the implementation and explain the profit sharing ratio for Hajj savings products at Bank Syariah Indonesia KCP Stabat in an Islamic economic perspective. The type of research used is qualitative research using field research models. Data collection techniques using observation, interviews, documentation. The steps used in analyzing the data are data reduction, data presentation, and drawing conclusions. The results of the study show that the Hajj savings product at Bank Syariah Indonesia KCP Stabat has used the mudharabah mutlaqah contract in carrying out its operations. From the results of managing the mudharabah funds, Bank Syariah Indonesia KCP Stabat will share the profits with the owners of the funds according to the ratio agreed at the beginning of the account opening contract, which is 15%: 85%. The distribution of the ratio of mabrur savings products carried out by Bank Syariah Indonesia KCP Stabat to its customers implements a revenue sharing profit sharing system. This principle has the meaning that there is a distribution of results, income or income between shohibul maal (customers) and mudharib (Bank Syariah Indonesia KCP Stabat) which is based on the total of all income before deducting the costs that have been incurred.